MUTATION ON WD DIPEPTIDE MOTIFS OF THE p48 SUBUNIT OF CHROMATIN ASSEMBLY FACTOR-1 CAUSING VIABILITY AND GROWTH OF DT40 CHICKEN B CELL LINE - Ahyar Ahmad; Harningsih Karim (Indonesian Journal of Chemistry, 2010)
Chromatin assembly factor-1 (CAF-1), a protein complex consisting of three subunits, p150, p60, and p48, is highly conserved from yeast to humans and facilitated nucleosome assembly of newly replicated DNA. The p48 subunit, CAF-1p48 (p48), with seven WD (Trp-Asp) repeat motifs, is a member of the WD protein family. The immunoprecipitation experiment revealed that ß-propeller structure of p48 was less stringent for it's binding to HDAC-1, but more stringent for its binding to both histones H4 and CAF-1p60 but not to ASF-1, indicating that the proper ß-propeller structure of p48 is essential for the binding to these two proteins histone H4 and CAF-1p60. Complementation experiments, involving missense and truncated mutants of FLAG-tagged p48, revealed that mutations of every of seven WD dipeptide motifs, like both the N-terminal and C-terminal truncated mutations, could not rescue for the tet-induced lethality. These results indicate not only that p48 is essential for the viability of vertebrate cells, although the yeast p48 homolog is nonessential, but also that all the seven WD dipeptide motifs are necessary for the maintenance of the proper structure of p48 that is fundamentally important for cell viability.